Baicalein antagonizes acute megakaryoblastic leukemia in vitro and in vivo by inducing cell cycle arrest. Issue 1 (December 2016) - Yu, Chunjie; Zeng, Jiancheng; Yan, Zhenzhen; Ma, Zi; Liu, Shangqin; Huang, Zan
Abstract Background The prognosis of acute megakaryoblastic leukemia (AMKL) is really dismal, which urges for development of novel treatment. Baicalein is one type of flavonoids extracted fromScutellaria baicalensis Georgi (Huang Qin). It inhibited cell proliferation and subcutaneous tumor formation of many tumor cell lines. However, whether baicalein possesses anti-AMKL activities has not been tested. Results We found that baicalein potently inhibited proliferation of multiple AMKL cells including CMK, CMY, Y10, 6133, and 6133 MPL/W515L due to apoptosis and cell cycle arrest at G1 phase. Unexpectedly, caspase inhibitor z-VAD-fmk did not restore cell proliferation. In contrast, ectopic expression of Cyclin D1 efficiently antagonized the inhibitory effect of baicalein. In addition, baicalein induced differentiation of 6133 MPL/W515L cells. Finally, baicalein promoted mice survival and reduced disease burden in a mouse model of AMKL. Conclusions Baicalein possesses potent anti-AMKL activity in vitro and in vivo. Baicalein may be a potent reagent for AMKL therapy.